Trend analysis of leprosy indicators in a hyperendemic Brazilian state, 2001-2015 - Jefferson de Jesus Silva Anchieta; Léa Márcia Melo da Costa; Leonardo Costa Campos; Maurício dos Remédios Vieira; Osvaldina Silva Mota; Otaliba Libânio Morais Neto; Marta Rovery de Souza; Rafael Alves Guimarães
ABSTRACT OBJECTIVE To analyze the temporal trend of leprosy indicators in a hyperendemic state of Brazil, from 2001-2015. METHODS This is a time-series study of leprosy indicators in the state of Maranhão, Northeastern region of Brazil. The study used data from the Brazilian National System of Reportable Diseases, for the period between 2001 and 2015. The following indicators were evaluated: (i) detection coefficient in the general population; (ii) detection coefficient in people under 15 years old; (iii) rate of cases with grade 2 physical disability in the diagnosis; (iv) rate of examined contacts, and (v) proportion of healing . The Prais-Winsten regression model was used for trend analysis. Analyses were performed for the state and by each health region. RESULTS 77,697 leprosy cases were analyzed in the general population and 7,599 in individuals under 15 years old. The detection coefficient in the general population ranged from 80.7/100 thousand inhabitants in 2001 to 51.2/100 thousand inhabitants in 2015. The coefficient in the general population presented a downward trend (annual percentage variation [APV] = -2.98; 95%CI -4.15- -1.79). For the population under 15 years old, the rate was 24.9/100 thousand inhabitants in 2001, and 19.9/100 thousand inhabitants in 2015, with downward trend (APV = -3.07; 95%CI -4.95- -1.15). It was observed upward trend in rate of contacts examined (APV = 2.35; 95%CI 0.58-4.15) and rate of cases with grade 2 disability (APV = 2.19; 95%CI 0.23-4.19). Stationary trend was observed in the proportion of healing (APV = -0.10; 95%CI -0.50-0.30). Regional differences were found in the performance of the indicators. CONCLUSIONS A downward trend for the detection coefficients in the general population and in individuals under 15 years old was found in Maranhão. Despite this result, the rates are still very high, demanding efforts from all spheres of public administration and health professionals to reduce the burden of the disease in the state.